PENINGKATAN PRESTASI BELAJAR PPKN MELALUI METODE PROBLEM BASED LEARNING BERBANTUAN MEDIA KAHOOT DI KELAS V SEKOLAH DASAR - Safaat Zuhri (Universitas Muria Kudus, 2023)
This study aims to improve Civics learning achievement through the Problem-Based Learning method assisted by the Kahoot media class V Elementary School for the 2021/2022 academic year. The research was carried out in March 2022. The subjects in the study were fifth-grade students. The study used classroom action research procedures including planning, implementation, observation and reflection. Data analysis is qualitative data. The results of the student’s learning achievement in the initial test showed that of the 18 students, 10 were completed with a percentage of 55.5% and 8 were not completed with a percentage of 44.3%. The first cycle data showed that 13 students completed the percentage of 72.22% and 5 did not complete the percentage of 27.77%. In the second cycle there was an increase in 17 students who completed the percentage of 94.4% 1 did not complete the percentage of 5.55. Thus learning achievement increases.